Multi‐GCM by multi‐RAM experiments for dynamical downscaling on summertime climate change in Hokkaido. (27th January 2015) - Inatsu, Masaru; Sato, Tomonori; Yamada, Tomohito J.; Kuno, Ryusuke; Sugimoto, Shiori; Farukh, Murad A.; Pokhrel, Yadu N.; Kure, Shuichi
Abstract The experiments with three general circulation models (GCMs) by three regional atmospheric models (RAMs) for the dynamical downscaling (DDS) have been performed to evaluate the uncertainty in the global warming response during summertime in Hokkaido, Japan. The results of a 10‐year RAM integration nested into GCM under present or future climate conditions were synthesized after applying bias correction. For the target decades during which the global‐mean temperature increases by 2 K in each GCM, the DDS results indicate that surface air temperature and precipitation mostly depend on the GCM imposed as the lateral boundary condition.